Cities at war in early modern Europe - Pollak, Martha D. (Cambridge Univ. Press, 2010)
"Between 1550 and 1700, artillery siege warfare transformed the European city, which was theorized, fortified, violated, rebuilt, and celebrated by leading artists and architects. The fortified perimeter, with its regular bastions, redefined the identity of the early modern city. Military planning also generated new forms of urban spaces, such as the orderly grid, the tree-lined avenue, the great central square dominated by triumphal sculpture, and the greenbelt that provided clear boundaries and controlled viewpoints. In The city at war in early modern Europe, Martha Pollak offers a pan-European, richly illustrated study of early modern military urbanism, an international style of urban design characterized by uniformity, geometrical clarity, architectural economy, and unadorned monumentality. Pollak examines this new urbanism as visualized by engravers, painters, and cartographers in accurate plans and powerful panoramic views. Her comparative, transnational study ranges from Britain to the Ottoman Empire, and from Malta to Scandinavia, and focuses on major centers--Naples, Paris, Antwerp, Stockholm--and "fortress cities" such as Valletta and Palmanova, which are still defined by their immense, geometrically perfect fortifications"--Provided by publisher